Why do people purchase from food delivery apps? A consumer value perspective - Tandon Anushree; Kaur Puneet; Bhatt Yogesh; Mäntymäki Matti; Dhir Amandeep (Elsevier, 2022)
Abstract
Consumers are increasingly using food delivery apps (FDAs) to facilitate convenient and quick food delivery. Yet, the existing research offers a limited understanding of consumers’ behavioral responses to the visibility and values derived from FDAs. Our study utilized the theory of consumption values (TCV) to examine associations between FDA visibility, consumption values, and purchase intentions. The mediating role of consumption values and the moderating role of attitude was also studied. A qualitative study was conducted with 15 FDA consumers to derive context-specific consumption values. Responses from 355 FDA consumers from the United States of America (USA) were obtained through Prolific and analyzed using structural equation modeling. Visibility acted as an antecedent of all consumption values and significantly influenced purchase intentions. Attitude also positively and significantly influenced purchase intentions. Consumption values partially mediated the association between visibility and purchase intention, while attitude negatively moderated the relationship that purchase intention has with visibility and preference value. These findings have important implications for theory and practice.